Effects of Lysinibacillus sphaericus HY3 on the gut microbiota, metabolism and resistance to Aeromonas hydrophila infection of adult zebrafish (Danio rerio) - Haoyu Qiu; Yuting Zhu; Hanying Wang; Chenzhi Tao; Zhiqiang Ran; Jiahang Xu; Junbo Wang; Shiyong Huang; Ping Wang (Aquaculture Reports)
This study aimed to elucidate the effects of Lysinibacillus sphaericus HY3 on the growth performance, liver antioxidant and immune capabilities, intestinal morphology, intestinal digestive enzyme activities, gut microbiota, metabolism, and disease resistance of adult zebrafish. Three hundred and sixty zebrafish with an initial body weight of 252 ± 5.0 mg were randomly and equally divided into four groups: ZF0 group (the control group), ZF5 group (105 CFU/mL L. sphaericus HY3), ZF6 group (106 CFU/mL L. sphaericus HY3), and ZF7 group (107 CFU/mL L. sphaericus HY3). Each group included three biological replicates. The experimental period lasted for 33 days. The results indicated that the survival rate, weight gain rate (WGR), and specific growth rate (SGR) showed an increasing trend with the increasing concentration of L. sphaericus HY3. As the concentration of L. sphaericus HY3 increasing, the superoxide dismutase (SOD) and catalase (CAT) activities showed a significant quadratic increase (P < 0.05), the content of malondialdehyde (MDA) showed a significant linear decrease (P < 0.05), and the activities of lysozyme (LZM) and glutamate pyruvate transaminase (GPT) showed a significant linear and quadratic increase (P < 0.05). As the concentration of L. sphaericus HY3 increasing, the levels of lipase (LPS), villus height, crypt depth, and the number of goblet cells all showed significant linear increase (P < 0.05), while the trypsin activity showed a significant quadratic increase (P < 0.05). Analysis of the gut microbiota revealed that the relative abundances of Fusobacteriota, Cetobacterium, and Gemmobacter showed a significant quadratic increase (P < 0.05) as the concentration of L. sphaericus HY3 increasing, while the relative abundance of Aeromonas showed a significant quadratic decrease (P < 0.05). Furthermore, 107 CFU/mL of L. sphaericus HY3 promoted the production of antioxidant and immune-related metabolites, such as Tuftsin, 5b-Cyprinol sulfate, Ubiquinone, and Ascorbate. Correlation analysis of differential gut microbiota with metabolites revealed that Lactobacillus, Prevotellaceae_UCG_001, and unclassified Muribaculaceae exhibited significant positive correlations with Dehydropipernonaline, (-)-(Z)-Tetrahydro-6-(2-pentenyl)-2H-pyran-2-one, and Fostriecin. Supplementation with 107 CFU/mL of L. sphaericus HY3 significantly improved the resistance of adult zebrafish to Aeromonas hydrophila (P < 0.05). In conclusion, L. sphaericus HY3 enhanced the digestive and absorptive capacities as well as the immunity of adult zebrafish by regulating the abundance of beneficial intestinal bacteria and the production of immune-related metabolites. Furthermore, a high concentration of L. sphaericus HY3 was more favorable to the disease resistance of adult zebrafish. This study laid a theoretical foundation for the application of L. sphaericus HY3 in practical aquaculture.